2006
DOI: 10.1002/pssb.200541287
|View full text |Cite
|
Sign up to set email alerts
|

Substantial pressure effect on the resistivity and Curie temperature for the diluted magnetic semiconductor Sb2–xVxTe3

Abstract: The influence of hydrostatic pressure on the electrical resistivity ρ and ferromagnetic transition temperature T C of bulk, single crystal Sb 1-x V x Te 3 with x = 0.03 is presented. Pressure strongly suppresses ρ at all temperatures, with an overall decrease of about 35% at 1.6 GPa. The peak in ρ, a signature of T C , moves to lower temperature with increasing pressure. An overall suppression of T C near 40% at 1.6 GPa is observed. The results are discussed within the context of a carrier-mediated ferromagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…The observed substantial pressure effect on Θ, dΘ/dP = −0.75 K/kbar, correlates both in sign and magnitude with the reported in Ref. [37] value of pressure effect on the Curie temperature T C for V-doped Sb 2 Te 3 compound, dT C /dP = −1.3 K/kbar, that suggests a common nature of magnetic interactions in both systems.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The observed substantial pressure effect on Θ, dΘ/dP = −0.75 K/kbar, correlates both in sign and magnitude with the reported in Ref. [37] value of pressure effect on the Curie temperature T C for V-doped Sb 2 Te 3 compound, dT C /dP = −1.3 K/kbar, that suggests a common nature of magnetic interactions in both systems.…”
Section: Discussionsupporting
confidence: 87%
“…[37] value of pressure effect on the Curie temperature T C for V-doped Sb 2 Te 3 compound, dT C /dP = −1.3 K/kbar, that suggests a common nature of magnetic interactions in both systems. Another principal parameter resulted from the data represented in figure 5 is the pressure derivative of the value χ 0 .…”
Section: Discussionmentioning
confidence: 89%
“…Ab initio calculations [13,29,30] and experimental XANES and XAFS studies [31,32] demonstrated that chromium ions substitute trivalent bismuth ions in the Bi 2 Se 3 lattice. In agreement with this conclusion, the chromium ions were often suggested to have a 3+ oxidation state [27,33]. In [27] the evaluated S was near 1.7.…”
supporting
confidence: 53%
“…To understand some of these issues the current research effort in spintronics materials is also directed toward the search for potential DMS hosts. Recently it was found experimentally [14] that the semiconducting tetradymite structure material Sb 2 Te 3 acts as a DMS with T c 20 K when doped with a few per cent of V atoms. Similarly, a recent, first principles calculation, [15] indicated that transition-metal-doped SiC may be ferromagnetic with T c very close to room temperature.…”
Section: Introductionmentioning
confidence: 99%